Safety and Efficacy of CT-Guided Central Venous Catheter Gastric Insufflation in Percutaneous Gastrostomy. (29th September 2022) - Zhang, Wen; Deng, Ruoyu; Chen, Boyu; Lv, Jialing; Zhu, Tingbiao; Huang, Meifang; Xu, Guoyu; Liu, Feineng; Zhang, Tengfei; Wang, Lin; Yue, Jun; Mu, Lixia; et al.
Abstract : Gastric insufflation for computed tomography (CT)-guided percutaneous gastrostomy is currently performed via a nasogastric tube or a Chiba needle. However, nasogastric tube placement requires patient pharynx and esophagus, and Chiba needle use is associated with an increased risk of organ damage and prolonged operation time. Herein, we introduce a new method of gastric insufflation via a central venous catheter and explore its safety and efficacy by retrospective analysis of the clinical data of patients who underwent percutaneous gastrostomy using this method in our hospital from April 2021 to March 2022. The extracted data included the following: success rate, operation time, gastric insufflation time, radiation dose, postoperative pain score, and complications. We also compared the preoperative levels of several nutritional indicators (body mass index, hemoglobin, albumin, creatinine, and blood urea nitrogen) with those obtained 1 month postoperatively. A total of 12 patients underwent percutaneous gastrostomy under CT guidance using central venous catheter gastric insufflation. The surgery and gastric insufflation success rates were 100% both. The average operation time, gastric insufflation time, and effective radiation dose were 24.08 ± 5.25  min, 5.08 ± 2.50  min, and 14.16 ± 3.63  mSv, respectively. Based on the World Health Organization scale for pain assessment, five patients reported no postoperative pain and seven patients had mild pain. There were no serious complications, such as stoma infection, peritonitis, gastrointestinal perforation and bleeding, or embedding syndrome. All evaluated nutritional indicators showed improvement at 1 month postoperatively, with statistically significant differences compared to the preoperative values (p < 0.05 for all). In conclusion, CT-guided percutaneous gastrostomy with central venous catheter gastric insufflation is a safe, effective, and feasible minimally invasive treatment.